. Analysis of Financial Management in Micro, Small and Medium Enterprises (MSMEs) in North Luwu Regency - Alfiyyah, Ashma Fiya (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2025)
This research discusses financial management in micro, small and medium enterprises (MSMEs) in North Luwu Regency. The main problem in this research is that MSMEs do not really understand good financial management. Where there are 4 (four) indicators in financial management, namely financial planning, recording, reporting and controlling. This research aims to find out how financial management is implemented by MSMEs in North Luwu Regency. This type of research uses qualitative research. The data collection methods used are observation, interviews and documentation. The informants in this research were 10 (ten) MSME actors operating in the trade and services sector. The results of this research show that the majority of MSME actors in North Luwu Regency have implemented financial planning well, even though financial recording and reporting is still done in a simple way. MSMEs generally do not have complete financial reports and awareness of the importance of financial control is still low. This research recommends training and counseling from the government to increase MSME actors' understanding of effective financial management, in order to encourage the sustainability and growth of their businesses.